Social Media, Influencers and FOMO : Key Drivers of Generation Z’s Cryptocurrency Investment Behavior - Laury Khana Agricha Irti; Afriza Amir; Nur Ahmadi Bi Rahmani (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the influence of social media, influencers, and the fear of missing out (FOMO) phenomenon on cryptocurrency investment decisions. In the digital era, social media has become a key channel for information and communication, including in finance and investment. Influencers on platforms such as Instagram, Twitter, YouTube, TikTok, and Facebook often serve as sources of investment recommendations, particularly among Generation Z. At the same time, FOMO drives Generation Z to make investment decisions out of fear of being left behind by emerging trends. This research employs a quantitative method by distributing questionnaires to Generation Z respondents in Medan. The findings reveal that social media, influencers, and FOMO significantly affect investment decisions, with social media exerting the strongest influence in shaping quick and high-risk choices. Overall, the study shows that Generation Z’s cryptocurrency investment decisions are more emotionally driven—through social media, influencers, and FOMO—than based on rational information.